An Analysis of Indonesian Language Interference in English Writing Through Contrastive Error Analysis - Vivi Nurul Ilmi; Maimunah Apriani Ritonga; Sabila Khoiroh Siregar; Teguh Amanda Batubara; Syahrul Ramadhan (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study investigated Indonesian language interference in students’ English writing through the use of Contrastive Error Analysis. The study aimed to identify the forms of Indonesian language interference, analyze its influence on students’ writing, and describe the types of errors found in the data. A descriptive qualitative research design was employed, and the data consisted of 15 English sentences collected from students’ written assignments. The data were analyzed using Error Analysis and Contrastive Analysis procedures to identify and explain the errors. The findings revealed four types of errors: misformation, omission, misordering, and addition. Misformation was the most dominant error type, with 8 occurrences, followed by omission (4), misordering (2), and addition (1). The analysis also showed that intralingual errors (10 occurrences) were more frequent than interlingual errors (5 occurrences). The study concludes that students’ writing errors were influenced by both Indonesian language interference and incomplete mastery of English grammar, although intralingual factors were more dominant.